TOWARDS PROACTIVE MONITORING STRATEGIES IN COMMUNICATION DECISION-MAKING: A SOCIAL MEDIA ANALYSIS APPROACH - Heru Yulianto; Dio Bryan; Joko Purwanto; Harmonis (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
This study examines the transformation of the digital communication strategy of the National Police of the Republic of Indonesia (Polri) in dealing with fluctuating public opinion dynamics in the era of information disruption. In the midst of the phenomenon of viral-based justice, the legitimacy of law enforcement institutions increasingly depends on the speed and accuracy of responses to issues. Using the conceptual framework of reputation management and crisis communication, this study aims to evaluate the effectiveness of the social media monitoring system implemented by the Public Relations Division of the National Police and formulate a more adaptive strategy model. Through a descriptive qualitative approach, data was collected through in-depth interviews, participatory observations, and documentation studies to map the ongoing public communication workflow. The findings of the study reveal that the current monitoring mechanism is still dominated by manual and partial data collection, which has implications for communication response patterns that tend to be reactive—waiting for issues to peak before being mitigated. The study identified a significant gap between the volume of social media big data and conventional information processing capacity. As a strategic solution, this study recommends the integration of advanced analytical technologies, especially Natural Language Processing (NLP) and Machine Learning, into the National Police's communication ecosystem. This integration is expected to transform the communication paradigm from simply responding to crises to detecting potential crises early (pre-crisis), enabling proactive, measurable, and evidence-based decision-making to maintain public trust.